Ras Shamra Parallels. The Texts from Ugarit and the Hebrew Bible, Vol. 1 (1972)
Associate Editors: F. Brent Knutson and Donn F. Morgan; I. Antoon Schoors, Literary Phrases; II. Mitchell Dahood, with the collaboration of Tadeusz Penar, Ugaritic-Hebrew Parallel Pairs; III. Jack M. Sasson, Flora, Fauna and Minerals; 2 further volumes planned, to treat Motifs, Formulae, Institutions, Place Names, Personal Names, Divine Names, Wisdom, Literary Structures.